Linking stress coping styles with brain mRNA abundance of selected transcripts for Senegalese sole (Solea senegalensis) juveniles - Fatsini, Elvira (2020)
In fish, proactive and reactive individual stress copying styles (SCS) have been used to resolve variation in molecular expression data. Stress coping styles have been previously described in several stages of Solea senegalensis by validating for the species the use of standard behavioural screening tests. The present study aimed to link behavioural SCS tests with brain transcript abundance in early Senegalese sole juveniles in order to observe the natural variation in a molecular pathway in this species. A total of 50 juveniles were subjected to three individual behavioural (Restraining, New environment and Confinement) and one group (Risk-taking) screening tests. The fish were classified in SCS categories by applying a hierarchical cluster to the variable "Total activity" (the total activity time that the fish was moving in each individual test). Three categories were defined, proactive, intermediate and reactive sole. Six transcripts were chosen and tested, one related to basic metabolism (gapdh-2), three to feeding behaviour (per1, igf-Ia, pparß) and two to the stress response (crh-BP and hsp90aa) in 30 juveniles (10 individuals per SCS category) using rt-qPCR to observe differences in the abundance of those transcripts among SCS. Four transcripts were differentially expressed (DETs) among them. The transcript gapdh-2 showed up-regulation for proactive and intermediate SCS sole while reactive individuals showed down-regulation. Target mRNAs per1, igf-Ia and pparß, showed different levels of up-regulation for proactive and reactive fish while intermediates were highly down-regulated. Surprisingly no differences in stress related transcripts were observed. Correlations were found between variation in coping styles and variation in the abundance of mRNAs involved in important biological functions in Senegalese sole. These results are the first evidence of the relationship between the behavioural individual variation and the fluctuation in brain transcripts abundance in Senegalese sole.